Results from the third Scottish National Prevalence Survey: is a population health approach now needed to prevent healthcare-associated infections?. Issue 3 (July 2018) - Cairns, S.; Gibbons, C.; Milne, A.; King, H.; Llano, M.; MacDonald, L.; Malcolm, W.; Robertson, C.; Sneddon, J.; Weir, J.; Reilly, J.
Summary: Background: Healthcare-associated infections (HCAIs) are a major public health concern and a significant cause of morbidity and mortality. A robust and current evidence base that is specific to local, national and Europe-wide settings is necessary to inform the development of strategies to reduce HCAI and contain antimicrobial resistance. Aim: To measure the prevalence of HCAI and antimicrobial prescribing and identify key priority areas for interventions to reduce the burden of infection. Methods: A national rolling point-prevalence survey (PPS) in National Health Service (NHS) acute, NHS non-acute, NHS paediatric, and independent hospitals was carried out between September and November 2016 using the European Centre for Disease Prevention and Control protocol designed for the European PPS. Findings: The prevalence of HCAI was 4.6%, 2.7%, and 3.2% in acute adults, paediatric and non-acute patient groups, respectively. The most frequent HCAI types reported in adult patients were urinary tract infection and pneumonia. The prevalence of antimicrobial prescribing was 35.7%, 29.3%, and 13.8% in acute adults, paediatric, and non-acute patient groups, respectively. Respiratory, skin and soft tissue, gastrointestinal, and urinary tract infections were the most common infections being treated at the time of survey. Conclusion: HCAI continues to be a public health concern in Scotland. Urinary tract infection and pneumonia continue to place a significant burden on patients and on healthcare delivery, including those that develop in the community and require hospital admission. A broader population health approach which focuses on reducing the risk of infection upstream would reduce these infections in both community and hospital settings.